Ubiquitin ligases at the nexus of plant responses to biotic and abiotic stresses. Issue 2 (5th August 2022) - Stone, Sophia L.
Abstract: Plants must cope with an ever-changing environment, including concurrent biotic and abiotic stresses. The ubiquitin–proteasome system (UPS) is intricately involved in regulating signaling events that facilitate cellular changes required to mitigate the detrimental effects of environmental stress. A key component of the UPS are ubiquitin ligases (or E3s) that catalyze the attachment of ubiquitin molecules to select substrate proteins, which are then recognized by the 26S proteasome for degradation. With the identification of substrate proteins, a growing number of E3s are shown to differentially regulate responses to abiotic as well as bioitic stresses. The review discusses select E3s to illustrate the role of ubiquitin ligases as negative and/or positive regulators of responses to both biotic and abiotic stresses.